GAMBARAN PEMANFATAAN PEMBIAYAAN BANTUAN OPERASIONAL KESEHATAN MELALUI PROGRAM LAYANAN USIA LANJUT DI PUSKESMAS FONUANSINGKO - Marwani (Forind Press, 2026)
Facilities and infrastructure, planning, and implementation are crucial components in supporting the success of the Elderly BOK program at the Community Health Center (Puskesmas). Evaluation of these three aspects is necessary to ensure service quality, targeted accuracy, and program effectiveness in meeting the health needs of the elderly. The purpose of this study was to determine the utilization of health operational assistance funding through the elderly service program at the Fonuansingko Community Health Cente. This study used a descriptive quantitative method with a sample of 31 respondents selected purposively. The research instrument was a structured questionnaire covering three main variables: facilities and infrastructure, planning, and implementation of the Elderly BOK program. Data were analyzed descriptively using frequency distributions and percentages to reflect the conditions on the ground. The results showed that facilities and infrastructure were adequate (>80%), but some specific facilities were not evenly distributed. Planning was complete but monitoring and facilities needed to be strengthened. Implementation was on schedule with good results, although supervision still needed to be improved. In conclusion, all three variables were in the good category and mutually supported the success of the Elderly BOK program. Improvements are needed in the equal distribution of special facilities, strengthening of monitoring-evaluation plans, and increasing supervision of implementation to ensure the quality and sustainability of services.